Knocking on the Ivory Tower: ?The Experience of Ex-Convicts Applying for Tenure-Track University Positions - Murphy, Daniel S. (2010)
This article reports the results of an investigation involving a select number of former prisoners with completed PhDs, who applied for work as tenure-track criminology/criminal justice professors. It attempts to place into context the literature on ex-convicts’ employment, the hiring process at academic institutions, and the experiences of ex-convicts with PhDs competing for academic jobs at colleges and universities. The findings are based on the personal experiences of ex-convict university professors, gathered through a questionnaire. Analysis of responses reveals little evidence of perceived prejudice against former criminals at the recruitment and interview stages. However, the hiring stage may be more problematic. In part, results suggest that the impact of a criminal conviction on employment chances may depend on the point at which disclosure about a felonious past is made